Silk & Sinews The UK debut of Japan's Nihon Buyo - Brennan, Mary (Dance Books Ltd., Alton,Hampshire (UK), 2005)
The UK debut of Japan's Nihon Buyo. PALABRAS CLAVE: japanese dance, Nihon Buyo, kabuki, Nishikawa Senzo.